Enhanced proton conductivity from phosphoric acid‐incorporated 3D polyacrylamide‐graft‐starch hydrogel materials for high‐temperature proton exchange membranes. Issue 16 (21st March 2014) - Qin, Qi; Tang, Qunwei; He, Benlin; Chen, Haiyan; Yuan, Shuangshuang; Wang, Xin
ABSTRACT To enhance anhydrous proton conductivity of high‐temperature proton exchange membranes (PEMs), we report here the realization of H3PO4‐imbibed three‐dimensional (3D) polyacrylamide‐graft‐starch (PAAm‐g‐starch) hydrogel materials as high‐temperature PEMs using the unique absorption and retention of crosslinked PAAm‐g‐starch to concentrated H3PO4 aqueous solution. The 3D framework of PAAm‐g‐starch matrix provides enormous space to keep H3PO4 into the porous structure, which can be controlled by adjusting crosslinking agent and initiator dosages. Results show that the H3PO4 loading and therefore the proton conductivities of the membranes are significantly enhanced by increasing the amount of crosslinking agent and initiator dosages. Proton conductivities as high as 0.109 S cm−1 at 180°C under fully anhydrous state are recorded. The high conductivities at high temperatures in combination with the simple preparation, low cost, and scalable matrices demonstrate the potential use of PAAm‐g‐starch hydrogel materials in high‐temperature proton exchange membrane fuel cells. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40622.